Effect of Artificial Aging on the Roughness and Microhardness of Sealed Composites - Catelan, Anderson [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundfeld, Renato Herman [UNESP]; Santos, Paulo Henrique dos [UNESP] (Wiley-Blackwell, 2010)
Statement of the Problem:The application of surface sealant could improve the surface quality and success of composite restorations; however, it is important to assess the behavior of this material when subjected to aging procedures.Purpose:To evaluate the effect of artificial aging on the surface roughness and microhardness of sealed microhybrids and nanofilled composites.Materials and Methods:One hundred disc-shaped specimens were made for each composite. After 24 hours, all samples were polished and surface sealant was applied to 50 specimens of each composite. Surface roughness (Ra) was determined with a profilometer and Knoop microhardness was assessed with a 50-g load for 15 seconds. Ten specimens of each group were aged during 252 hours in a UV-accelerated aging chamber or immersed for 28 days in cola soft drink, orange juice, red wine staining solutions, or distilled water. Data were analyzed by two-way analysis of variance and Fischer's test (alpha = 0.05).Results:Artificial aging decreased microhardness values for all materials, with the exceptions of Vit-l-escence (Ultradent Products Inc., South Jordan UT, USA) and Supreme XT (3M ESPE, St. Paul, MN, USA) sealed composites; surface roughness values were not altered. Water storage had less effect on microhardness, compared with the other aging processes. The sealed materials presented lower roughness and microhardness values, when compared with unsealed composites.Conclusions:Aging methods decreased the microhardness values of a number of composites, with the exception of some sealed composites, but did not alter the surface roughness of the materials.CLINICAL SIGNIFICANCEThe long-term maintenance of the surface quality of materials is fundamental to improving the longevity of esthetic restorations. In this manner, the use of surface sealants could be an important step in the restorative procedure using resin-based materials.(J Esthet Restor Dent 22:324-331, 2010).